Python and SQL Bible. - Cuantum Technologies LLC; PACKT (GB: Packt, 2024)
Dive into comprehensive learning with Python and SQL Bible. This course covers everything from Python fundamentals to advanced SQL, empowering technical professionals with essential programming and data analysis skills. Key Features Comprehensive coverage of Python and SQL from basics to advanced techniques. Equip yourself with essential programming and data analysis skills for the tech industry. Learn through detailed explanations, interactive exercises, and real-world projects. Book Description Embark on a transformative journey with this course designed to equip you with robust Python and SQL skills. Starting with an introduction to Python, you'll delve into fundamental building blocks, control flow, functions, and object-oriented programming. As you progress, you'll master data structures, file I/O, exception handling, and the Python Standard Library, ensuring a solid foundation in Python. The course then transitions to SQL, beginning with an introduction and covering basics, and proceeding to advanced querying techniques. You'll learn about database administration and how Python integrates seamlessly with SQL, enhancing your data manipulation capabilities. By combining Python with SQLAlchemy, you'll perform advanced database operations and execute complex data analysis tasks, preparing you for real-world challenges. By the end of this course, you will have developed the expertise to utilize Python and SQL for scientific computing, data analysis, and database management. This comprehensive learning path ensures you can tackle diverse projects, from basic scripting to sophisticated data operations, making you a valuable asset in the tech industry. You'll also gain hands-on experience with real-world datasets, enhancing your problem-solving skills and boosting your confidence. What you will learn Understand and apply Python fundamentals. Master control flow and object-oriented programming in Python. Perform advanced SQL queries and database administration. Integrate Python with SQL for enhanced data manipulation. Conduct complex data analysis using Python and SQLAlchemy. Manage files and handle exceptions in Python effectively. Who this book is for This course is ideal for a wide range of learners, including technical professionals, aspiring data scientists, software developers, and database administrators looking to enhance their skill set. It's perfect for beginners with little to no programming experience, as well as those with some background in coding who want to deepen their knowledge of Python and SQL. Additionally, it serves business analysts and IT professionals aiming to leverage data analysis and database management in their roles.
Data in extended ASCII character set.
Mode of access: Internet.